Comparison of Estimated Glomerular Filtration Rate at 60 Ml/Min using MDRD and CG Equations with Blood Urea Nitrogen, Creatinine and Albuminuria in Type 2 Diabetic Patients - Songthananit, Bhurit; Khowtap, Jintana; Kangwantrakul, Wisut; Proungvitaya, Siriporn; Promdee, Limthong (Srinagarind Medical Journal, 2015)
Objective: Estimated Glomerular Filtration Rate (eGFR) has been routinely used to assess renal function nowsday. The aimed of this study was to evaluate eGFR derived from Modification of Diet in Renal Disease (MDRD) and of Creatinine Clearance (CCr) obtained from Crockcoft-Gault equation (CG) at filtration rate 60 ml/min compared to albuminuria (urine albumin creatinine ratio; UACR), creatinine (Cr), and blood urea nitrogen (BUN) in type 2 diabetic patients. Material and method: A retrospective study was performed in 238 type 2 diabetic patients (male 96, female 142) who attended diabetic clinic,Wattananakorn Hospital, Sakaeo Province, Thailand, between March – May, 2012. eGFR was calculated followed MDRD and CG formulas. The association of eGFR and UACR, Cr, and BUN was analyzed using X2-test Result: At eGFR ≥ 60 ml / min, MDRD was significant lower than those of CG (71 ± 10 ml/min/1.73 m2 & 78 ± 15 ml/min, p <0.001). However, MDRD were significant higher than CG (46 ± 10 ml/min/1.73 m2 & 43 ± 11 ml/min) at eGFR <60 ml/min (p < 0.016). The level of BUN, Cr, UACR of MDRD was not different from those of CG equation. MDRD and CG associated with BUN, Cr, but not microalbuminuria at eGFR 60 ml/min. Conclusion: The different of eGFR calculated by MDRD and CG equation was found at 60 ml/min. However, the level of BUN, Cr and UACR was not different between both equations. Therefore, BUN, Cr and UACR may not be reflected eGFR. In addition, eGFR 60 ml/min of both formulas relates to BUN, Cr, but not microalbuminuria